Introducing initial material and producing sterile form of sugar sorghum (Sorghum saccharatum (L.) Pers.) - В. І. Войтовська; Л. І. Сторожик; Т. М. Недяк (Plant Varieties Studying and Protection)
The article highlights summary of initial material introduction and of generation of sterile form of sugar sorghum, its ground germination capacity and viability of the seed in various fractions. This has scrutinized impact of various chemical reagents and expositions the yield of sterile and viable explants.